Horse-drawn wagons by camp on beach at the Lakeside Mine, near Penny River, September 17, 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Camp on Beach, Lakeside Mine near Penny River, Nome, Alaska. Sept. 17th 1905. Photo by F.H. Nowell 1905. 4429 Penny River flows into Norton Sound, 10 miles west of Nome. (pg. 748) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number